Ego vs The Unconscious: A Psychoanalytic Reading of Unsolved Trauma in Jojiâ€™s Past Wonâ€™t Leave My Bed - T. Thyrhaya Zein; Tania Chelsea Sinaga; Nasya Salsabila; Ayu Lestari situmorang; Naura Maesa; Gabrielle Angelika Siahaan (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2026)
This study aims to analyze the representation of the conflict between the ego and the unconscious, as well as the dynamics of unresolved trauma, in the lyrics of Jojiâ€™s song â€œPast Wonâ€™t Leave My Bed.â€ Additionally, this study aims to identify how these psychological patterns consistently emerge through their connection to other songs, such as â€œGlimpse of Us,â€ â€œWill He,â€ and â€œSlow Dancing in the Dark.â€ This study employs a qualitative approach using text analysis grounded in Sigmund Freudâ€™s psychoanalytic theory. The primary data, consisting of song lyrics, were analyzed through documentation and literature review techniques, then processed using data analysis steps according to Miles, Huberman, and SaldaÃ±a, as well as Creswell. The analysis was conducted thematically to identify patterns of trauma representation, including the persistence of the unconscious, intrapsychic conflict, the emergence of intrusive thoughts, superego pressure, and conditions of psychological helplessness. The results of the study indicate that trauma in song lyrics is not only represented as an emotional experience but also as a complex and recurring psychological process. The conflict between the ego and the unconscious is evident through the individualâ€™s inability to let go of the past, which continues to intrude into consciousness. These findings confirm that unresolved traumatic experiences can lead to anxiety, emotional dependency, and psychological imbalance. Thus, this study reinforces the relevance of the psychoanalytic approach in the study of modern music while demonstrating that song lyrics can reflect real and profound psychological states. Keywords: psychoanalysis, trauma, unconscious, song lyrics, intrapsychic conflict